THE INFLUENCE OF POLITICAL SOCIALIZATION AGENTS ON POLITICAL PARTICIPATION OF PAKISTANI YOUTHS - Sumera Memon; Mohd. Sobhi Bin Ishak; Norsiah Binti Abdul Hamid (Lingkar Studi Komunikasi (LISKI), 2017)
Young people are often characterized as apathetic and disconnected from the political world. Undoubtedly, their low rate of participation in general elections has increased concerns amongst researchers as well as policy makers. This concern has stimulated researchers to explore the factors which weaken or discourage youth engagement in political activities. Thus, this study assesses the role of family communicative environment, peer group communicative environment and school communicative environment as types of political socialization agents of political participation of youths. A cross-sectional survey was conducted among 288 social science students in Pakistan. Questionnaires were used to collect data and the collected data was analyzed using SPSS 23. The findings revealed that family communicative environment and peer group communicative environment positively influence the political participation of youths. However, school communicative environment was found to influence political participation negatively. This study provides an empirical justification for the potential of family and peer group as agents of political socialization for enhancing political activities among youth in Pakistan.